Eggshell integrated GelMA/CSMA/HyMA hybrid hydrogels for cell therapy/tissue engineering - Yuce-Erarslan, Elif; Izbudak, Burcin; Kizilkurtlu, Ahmet Akif; Topal, Merve; Akpek, Ali; Bal-Ozturk, Ayca (WILEY, 2023)
The use of biocompatible materials with improved behaviors for potential applications in the area of tissue engineering has increased as the developments in biomaterials have increased in recent years. Current approaches concentrate on hybrid combinations of synthetic and natural polymers. In this context, obtaining porous scaffolds with good mechanical properties is still challenging. Herein, a hybrid tissue scaffold consisting of methacrylated gelatin (GelMA), methacrylated chondroitin sulfate (CSMA), methacrylated hyaluronic acid (HyMA) and eggshell particles with enhanced pore morphology and mechanical property was fabricated by photo-polymerization. The effect of different amounts of eggshell particles on the behaviors of hybrid hydrogel scaffolds was investigated. It was determined by scanning electron microscope analysis (SEM) that the particles were well-dispersed and triggered the formation of an interconnected porous structure in the hybrid tissue scaffold containing 10% by weight of eggshell particles. It was concluded that the mechanical behaviors of the hybrid tissue scaffold containing 10% by weight of eggshell particles improved by 47% compared to the neat hydrogel scaffold. There were no toxic effects of eggshell particles-integrated scaffolds against osteoblast cells. In addition, cells successfully adhered onto the scaffolds and proliferated. Consequently, GelMA/CSMA/HyMA scaffolds containing 10% eggshell particles were found to be biocompatible and suitable for cell therapy and tissue engineering applications.
Keywords: eggshell; methacrylated chondroitin sulfate; methacrylated gelatin; methacrylated hyaluronic acid; tissue engineering; INTERPENETRATING POLYMER NETWORK; HYALURONIC-ACID; MECHANICAL-PROPERTIES; PHASE-SEPARATION; POROUS SCAFFOLDS; TISSUE; GELATIN; NANOPARTICLES; COMPOSITES; WASTE; Polymer Science